2015
DOI: 10.1186/s12909-015-0313-6
|View full text |Cite
|
Sign up to set email alerts
|

Challenging cases of professionalism in Japan: improvement in understanding of professional behaviors among Japanese residents between 2005 and 2013

Abstract: BackgroundProfessionalism is deemed as the basis of physicians’ contract with society in Japan. Our study in 2005, using a questionnaire with scenarios to professionalism, suggested that many physicians at various levels of training in Japan encounter challenges when responding to these common scenarios related to professionalism. It is unclear how medical professionalism has changed among Japanese residents in over time.MethodsWe conducted a follow-up survey about challenges to professionalism for Japanese re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 18 publications
0
8
0
Order By: Relevance
“…Chinese physicians could assert their own context-specific professional identity by establishing a professionalism framework that reflects cultural heritage [68], as has already been achieved at one Chinese medical school [69] and is reflected in experiences in the Middle East [17, 70]. Medical professionalism curricula can also be developed with consideration to local culture and needs, as has been demonstrated in Taiwan and Japan [71, 72]. Despite the modernization of medicine in China, traditional culture continues to influence perceptions of professionalism and societal expectations of physicians [69, 73].…”
Section: Discussionmentioning
confidence: 99%
“…Chinese physicians could assert their own context-specific professional identity by establishing a professionalism framework that reflects cultural heritage [68], as has already been achieved at one Chinese medical school [69] and is reflected in experiences in the Middle East [17, 70]. Medical professionalism curricula can also be developed with consideration to local culture and needs, as has been demonstrated in Taiwan and Japan [71, 72]. Despite the modernization of medicine in China, traditional culture continues to influence perceptions of professionalism and societal expectations of physicians [69, 73].…”
Section: Discussionmentioning
confidence: 99%
“…Our results suggested that many resident physicians in Japan encounter challenges when responding to the scenarios related to professionalism. 4,5 Compared to residents in the 2005 survey, those in the 2013 survey performed better for five scenarios (gifts, conflict of interest, confidentiality, impairment, and honesty) but not for the harassment scenario. Therefore, we proposed the implementation of a validated assessment tool and the improvement of curriculum for teaching professionalism to students and residents.…”
Section: Sexual Harassment: the Most Challenging Issue Of Medical Promentioning
confidence: 95%
“…The Barry Questionnaire is an assessment tool for evaluating views regarding professionalism; it is widely used in the US and Japan. [12][13][14] In a previous study, participants in the US performed better than participants in Japan in scenarios that were presented involving minor confidentiality and sexual harassment, but not for three scenarios (physician impairment, conflict of interest, and acceptance of gifts). [12] A recent study of novice physicians using the Barry Questionnaire mentions improvements in medical professionalism with respect to certain ethical challenges in Japan.…”
Section: Introductionmentioning
confidence: 80%
“…In addition, Kinoshita et al reported improved responses to the Barry Questionnaire by Japanese physicians. [14] The study by Barry et al [13] indicates that satisfaction with training in professionalism is significantly related to the amount of relevant coursework. Findings of the present study are consistent with those of the prior studies and extends them by demonstrating the further need for improvement in medical professionalism education for Japanese physicians in terms of confidentiality and sexual harassment.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation